Penguatan Verbal Dan Nonverbal Dalam Pembelajaran Bahasa Indonesia Di MTs Al-Azhar Rokan Hilir - Halimah, Siti; Yuliawan, Tri (Cetta: Jurnal Ilmu Pendidikan, 2025)
The decline in mutual education has always been a topic of discussion from various parties. Teachers have a very big responsibility in efforts to guide students towards their desired educational goals. There are several basic teaching skills that teachers must master, namely Skills in using verbal reinforcement and nonverbal reinforcement. Based on the results of observations made at MTs Al-Azhar Rokan Hilir to Indonesian language teachers who were teaching, researchers found symptoms, namely that the provision of verbal and non-verbal reinforcement by Indonesian language teachers had not been implemented optimally. This study aims to (1) describe the form of verbal reinforcement in Indonesian language learning for students of class VII MTs Al-Azhar Rokan Hilir. (2) describe the form of nonverbal reinforcement in Indonesian language learning for students of class VII MTs Al-Azhar Rokan Hilir. The approach to this research uses a qualitative descriptive approach, the data source is the class VII Indonesian language teacher. The data collection techniques used are observation techniques, interview techniques and questionnaire techniques. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The results of the research show that, (1) the class VII Indonesian language teacher has implemented verbal reinforcement in Indonesian language learning in the form of words of praise, words of appreciation and words of approval. (2) the class VII Indonesian language teacher has implemented non-verbal reinforcement in Indonesian language learning in the form of strengthening gestures, strengthening approaches, strengthening with touch, strengthening with fun activities, and strengthening in the form of symbols or objects. The reinforcement given is quite varied, but the diction needs to be developed again.